Application of Psychodrama and Object Relations Psychotherapy – An Integrated Approach to the Treatment of Bulimia Nervosa Based on Selected Elements of the Theory and the Author’s Own Experience - Izydorczyk, Bernadetta (IntechOpen, 2011)
None